Coping strategies, work-life balance programs, and their impact on professional performance of female lecturers in tertiary institutions in Anambra and Enugu States - Adaobi Jennifer Iloakasia (Piramida Akademi, 2024)
The dual responsibilities of career and parenting place significant demands on female lecturers, particularly in tertiary institutions, where academic expectations often collide with family obligations. In Anambra and Enugu States, female lecturers face unique challenges in balancing these roles, with many experiencing stress, burnout, and anxiety due to time constraints and societal expectations. The study used a descriptive survey approach to examine the coping strategies of female lecturers managing career and parenting responsibilities in tertiary institutions in Anambra and Enugu States, southeastern Nigeria. A total of 2,297 respondents from colleges of education, universities, and polytechnics participated. Data were collected using a validated 4-point Likert scale questionnaire, the